Margaret McCarthy. Mad Mädchen: Feminism and Generational Conflict in Recent German Literature and Film. New York: Berghahn Books, 2017. - Bridget Swanson (Studies in 20th & 21st Century Literature, 2018)
Review of Margaret McCarthy. Mad Mädchen: Feminism and Generational Conflict in Recent German Literature and Film. New York: Berghahn Books, 2017.
Keywords: Feminism; German Literature; German Film; Contemporary Studies